Study on the Population and Diversity of Arbuscular Mycorrhizal Fungi in the Rhizosphere of Piper nigrum in West Lampung Indonesia - Azzahra, Salwa; Rini, Maria Viva; Rusdi Evizal; Agus Karyanto (Asosiasi Mikoriza Indonesia, 2024)
The population and diversity of arbuscular mycorrhizal fungi (AMF) in soil vary greatly, influenced by biotic and abiotic factors. West Lampung Regency is a major prpper production center with distinct biotic and abiotic factors. These differences affect the diversity of AMF in pepper cultivation areas in West Lampung Regency. This study aimed to determine the differences in the population and diversity of indigenous AMF in the rhizosphere of pepper plants grown in monoculture and mixed cropping system. Soil sample were collected from monoculture and mixed pepper plantations. The AMF population in the samples was determined by isolating AMF spores from the soil using the wet sieving method. Trap cultures were established using soil samples from each plantation, using maize as the host plant, for duration of 3 months. The results showed that the AMF population in the rhizosphere of mixed pepper plantation was higher than that in monoculture plantations. Based on trap culture, 9 AMF types (S1, S2, S3, S4, S5, S6, S7, S8, and S9) were identified in mixed cropping system, while 5 AMF types (S4, S5, S6, S7, and S9) were found in monoculture plantations.